CAMERA DEVICE - PARK JU-UN; JANG SEONG-HA; JOO YANG-HYUN; KIN TETSU (2021)
A camera device according to an embodiment of the present invention comprises: a light-emitting part for changing the optical path of light according to a first control signal and outputting the light along a first optical path or a second optical path; a light-receiving part for receiving the light reflected from a subject and generating an electrical signal; and a controller for generating the first control signal which is provided to control whether the optical path of the light is changed to the first optical path or the second optical path, wherein the light-emitting part outputs the light in a first pattern along the first optical path or outputs the light in a second pattern along the second optical path. 根据本发明的实施例的摄像装置包括：发光部，该发光部用于根据第一控制信号改变光的光路并且沿着第一光路或第二光路输出光；光接收部，该光接收部用于接收由被摄体反射的光以及生成电信号；以及控制部，该控制部用于生成第一控制信号，该第一控制信号被提供成控制光的光路是否被改变为第一光路或第二光路，其中发光部沿着第一光路以第一图案输出光或者沿着第二光路以第二图案输出光。